2020
DOI: 10.18231/j.idjsr.2020.006
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary labial frenectomy by using conventional technique and laser – Report of two cases

Abstract: Aberrant frenum causes a problem of midline diastema which leads to unaesthetic smile for the patient. Orthodontic correction of midline diastema helps to create aesthetic smile but frenum attachment may interfere it. The labial frenectomy is the procedure performed to remove aberrant frenum attachment. This article presents two case reports of maxillary labial frenectomy by using conventional technique and Laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Secondary intention healing occurred because the gingiva can't closed completely [10]. Conventional technique results in a longitudinal surgical incision and scarring, that lead to various periodontal problems, scars and an unaesthetic appearance [11]. A number of modifications surgical techniques for removal of aberrant frenum including Miller's technique, V-Y plasty and Z-plasty, electrosurgery, lasers diode, carbon dioxide, Nd:YAG, Er:YAG and Er,Cr:YSGG.…”
Section: Resultsmentioning
confidence: 99%
“…Secondary intention healing occurred because the gingiva can't closed completely [10]. Conventional technique results in a longitudinal surgical incision and scarring, that lead to various periodontal problems, scars and an unaesthetic appearance [11]. A number of modifications surgical techniques for removal of aberrant frenum including Miller's technique, V-Y plasty and Z-plasty, electrosurgery, lasers diode, carbon dioxide, Nd:YAG, Er:YAG and Er,Cr:YSGG.…”
Section: Resultsmentioning
confidence: 99%
“…Heat produced by the laser makes small blood vessels and lymphatic vessels impassable thus reducing or eliminating blood flow and edema. [ 12 ] Thus controlled bleeding enables the surgeon to perform the operative procedure with ease and better visibility. The heat generated from the laser beam seals the sensory nerve endings which are responsible for the decreased or an absent post-operative pain.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the diode laser demonstrated negligible bleeding and a precise incision, lowered edema and scarring, reduced pain, faster healing response, and enhanced patient appreciation after analyzing both procedures. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation